Osborn waves on ECG in an elderly male of moderate hypothermia: a case report - Lamichhane, Kriti; Uprety, Bibhusa; Karki, Ashmita; Lamichhane, Kiran; Chhetri, Sundip Dware (Journal of General Practice and Emergency Medicine of Nepal, 2025)
Hypothermia is defined as a core body temperature below 35°C (95°F) and is associated with distinct Electrocardiography (ECG) abnormalities, most notably the Osborn wave (J wave). We report a case where a 76-year-old male presented to the Emergency Department with altered mental status following prolonged cold exposure on his balcony during winter, wearing minimal clothing. On admission, the patient’s rectal temperature was 87°F (30.6°C), consistent with moderate hypothermia. ECG revealed prominent Osborn waves, a pathognomonic feature of hypothermia. Active external rewarming using electric heated blankets resulted in gradual normalization of ECG findings and clinical stabilization. Osborn waves in hypothermia are a rare but critical ECG finding, often accompanied by systemic complications. Prompt rewarming is essential for reversing both clinical abnormalities. This case underscores the importance of early recognition and intervention in patients with hypothermia.